2014
DOI: 10.1155/2014/120173
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral Analysis, In Vitro Microbiological Evaluation, and Molecular Docking Studies of Some Novel 1-(1-Aryl-1H-tetrazol-5-yl)-2-(piperidin-1-yl)ethanone Derivatives

Abstract: A new series of novel heterocyclic compounds containing both tetrazoles and piperidine nuclei together, namely, 1-(1-aryl-1H-tetrazol-5-yl)-2-(piperidin-1-yl)ethanone (22–28), were synthesized by the treatment of the respective 2-chloro-1-(1-aryl-1H-tetrazol-5-yl)ethanone (15–21) with piperidine in acetonitrile for 6 h. A series of novel tetrazole substituted piperidine derivatives were synthesized and evaluated for their antimicrobial activity using serial dilution method. The structures of the synthesized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Recently, it has been reported that N -containing heterocycles are considered especially “privileged” structures for the synthesis and development of new drugs. 36,37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that N -containing heterocycles are considered especially “privileged” structures for the synthesis and development of new drugs. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that N-containing heterocycles are considered especially ''privileged'' structures for the synthesis and development of new drugs. 36,37 Compounds 7b (bis-benzyloxy substituent), 7f (benzodioxole substituent), and 7g (phenylpyrazole substituent) were the second most active in HepG2, T47D, and Jurkat cell lines, respectively.…”
Section: In Vitro Cytotoxic Activity In Tumor Cellsmentioning
confidence: 99%
“…Mesoridazine is a neuroleptic drug used in the treatment of schizophrenia, while raloxifene is used for the treatment of osteoporosis in post-menopausal-women. 5,6 Paroxetine is an antidepressant that contains an unprotected piperidine. 7…”
Section: Introductionmentioning
confidence: 99%
“…Among them, N -based heterocycles are especially important since many of the biologically active compounds such as alkaloids, glycosides, and hormones as well as some of the clinically used drugs carry N -containing heterocycles in their chemical structures. 1,2 As one of the N -based heterocycles, the piperidine ring system has been shown to possess various pharmacological effects such as antibacterial, antifungal, 3−5 anti-HIV, 6 antileishmanial, 7 anticancer, 8,9 renin inhibitory, 10 diuretic, and natriuretic 11 effects. Another N -containing heterocyclic structure, benzimidazole, is also known to have the ability to interact with biomolecules of living systems.…”
Section: Introductionmentioning
confidence: 99%